Tradisi Intelektual Islam Melayu-Indonesia: Adaptasi dan Pembaharuan - Fathurahman, Oman (Studia Islamika, 2001)
In the context of Islamic studies, the Malay-Indonesia region has for along time been the focus of attention of historians and researchers. There are many things that have generated interest in Islam in this region, particularly, amongst others, the unique qualities of this 'localized' Islam and the differences between these and those of Islam in other areas, in particular, in the Middle East. Besides this, the develpoment of Islam in the MAlay-Indonesia has passed through some fascinating phases that have not only been creative and dynamic, but have also provided great stimulus fot both religious discourse and religious practices.DOI: 10.15408/sdi.v8i3.685